2002
DOI: 10.2320/matertrans.43.2568
|View full text |Cite
|
Sign up to set email alerts
|

Hi-Nicalon<SUP>TM</SUP> Fiber-Reinforced CVI-SiC Matrix Composites: I Effects of PyC and PyC-SiC Multilayers on the Fracture Behaviors and Flexural Properties

Abstract: The flexural properties of 2D plain-woven Hi-Nicalon TM fiber reinforced SiC/SiC composites with various PyC and PyC-SiC multilayers were studied at ambient temperature. The composites were fabricated by chemical vapor infiltration process (CVI). The interlayers were deposited by isothermal CVI process from methane for PyC layer and CH 3 SiCl 3 (MTS) for SiC layer. The effects of the various interlayers on the fracture behaviors and flexural properties were investigated. The PyC layer thickness showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
2
24
1
Order By: Relevance
“…The composite with 150 nm PyC layer yielded an ISS ∼ 200 MPa, which seems to be the optimum value in term of the PLS for the 2D plain-woven Hi-Nicalon/SiC composites. These findings are in good agreement with the results in the study 4) on the flexural properties of these composites that the PLS showed sharp increase with the increase of the PyC layer thickness till ∼ 150 nm, and then decreased gradually. When the PyC layer was thicker than ∼ 200 nm, the PLS showed little change with the PyC layer thickness.…”
Section: )supporting
confidence: 92%
See 2 more Smart Citations
“…The composite with 150 nm PyC layer yielded an ISS ∼ 200 MPa, which seems to be the optimum value in term of the PLS for the 2D plain-woven Hi-Nicalon/SiC composites. These findings are in good agreement with the results in the study 4) on the flexural properties of these composites that the PLS showed sharp increase with the increase of the PyC layer thickness till ∼ 150 nm, and then decreased gradually. When the PyC layer was thicker than ∼ 200 nm, the PLS showed little change with the PyC layer thickness.…”
Section: )supporting
confidence: 92%
“…When single PyC or PyC-SiC multilayers were employed, the ISS was drastically decreased. It was found in the flexural properties study of these composites 4) that the interfacial debonding/sliding took place mostly at the interface adjacent to the first PyC layer (most near to the fiber). Rebillat et al 8) has also reported that the interfacial characteristics seemed to be related to the thickness of the first carbon layer on the fibers in as-received Nicalon fiber reinforced CVI SiC/SiC composites with (C-SiC) n interlayers.…”
Section: Iss and The Effects Of The Pyc Layermentioning
confidence: 97%
See 1 more Smart Citation
“…For conventional CVI-SiC/SiC composite systems, an optimum PyC interphase thickness range of 150-300 nm is reported for the best fracture behavior. [23][24][25][26] However, for application in fusion blankets, the minimum use of carbon constituents is preferred to optimize irradiation stability, chemical compatibility with coolants and/or breeding materials, tritium permeability, and electrical conductivity. The Generation Materials Transactions, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…During the past several tens of years, many efforts have been done to develop continuous silicon carbide fibers reinforced silicon carbide matrix (SiC/ SiC) composites for use in energy conversion systems, aviation and aerospace systems, etc. [1][2][3][4] SiC/SiC composites usually exhibit relatively large scatter in strength 5,6) because of the statistic distributions of the flaws and pores in the materials. Therefore, fabrication of SiC/SiC composites with dense and space homogeneous matrix densification is critical and remains one of the main current issues, especially when it comes to the evaluation of the strength and reliability of SiC/ SiC composites, which is necessary for critical engineering applications.…”
Section: Introductionmentioning
confidence: 99%